국소 허혈성 뇌손상 흰쥐 모델에서 경두개직류전기자극이 앞다리 운동감각 기능 증진에 미치는 효과 - 김기도(Gi-Do Kim); 심기철(Ki-Cheol Sim); 김경윤(Kyung-Yoon Kim) (한국콘텐츠학회 논문지, 11(4), 2011)
This study was to investigate the effect of improve forelimb sensorimotor function and neurotrophic factor(GAP-43) expression when differing an application time of tDCS in ischemic brain injury rat model(pre, $1^{st}$, $7^{th}$, $14^{th}$). Focal ischemic brain injury was induced in 80 Sprague-Dawley rats through middle cerebral artery occlusion(MCAO) by 'Longa' method. And then experimental groups were randomly divided into four groups; GroupI: MCAO induction, GroupII: application of tDCS(10 min) after MCAO induction, GroupIII: application of tDCS(20 min) after MCAO induction, GroupIV: application of tDCS(30 min) after MCAO induction. Modified limb placing test and single pellet reaching test were performed to test forelimb sensorimotor function. And the histological examination was also observed through the immunohistochemistric response of GAP-43(growth-associated protein-43) in the cerebral cortex. In modified limb placing test, groupIII(p<0.05) showed significantly improve than the other groups on $14^{th}$). day. In single pellet reaching test, groupIII(p<0.01) and groupIV(p<0.05) significantly improved on $14^{th}$) day. And in immunohistochemistric response of GAP-43, group III showed significantly positive response than the other groups on $14^{th}$ day. These results suggest that the intensity(0.1 mA)/time(20 min) condition of tDCS application has a significant impact on the sensorimotor functional recovery in focal ischemic brain injury rat models. 본 연구는 국소 허혈성 뇌손상 흰쥐 모델에서 tDCS의 자극 적용시간을 달리하였을 때, 앞다리 운동감각 기능변화와 신경영양인자(GAP-43)발현에 미치는 영향을 알아보고자 하였다. 뇌손상 모델은 Sprague -Dawley계 흰쥐 80마리를 'Longa'방법을 이용하여 중대뇌동맥(middle cerebral artery)을 폐색하여 유발하였고, 실험군을 4개로 나누었다; 실험군I은 허혈성 뇌손상 유발군(n=20), 실험군II는 허혈성 뇌손상 유발 후 tDCS(10분) 적용군(n=20), 실험군III은 허혈성 뇌손상 유발 후 tDCS(20분) 적용군(n=20), 실험군IV는 허혈성 뇌손상 유발 후 tDCS(30분) 적용군(n=20)으로 나누었다. 앞다리운동감각 기능검사를 위해 수정된 앞다리배치 검사와 단일 팰릿 닿기 검사를 실시하였으며, 신경가소성에 대한 면역조직화학적 검사로 운동감각 영역에서의 GAP-43 단백질 발현을 관찰하였다. 앞다리운동감각 검사는 14일에서 실험군III (p<0.05)이 다른 군들에 비해 유의한 차이를 보였으며, 단일 팰릿 닿기 검사는 14일에서 실험군III(p<0.01)과 실험군IV(p<0.05)에서 유의한 차이를 보였다. 또한, 면역조직학적 검사는 14일에 실험군III이 다른 군들에 비해 현저한 면역양성반응의 증가를 보였다. 따라서, 0.1 mA의 강도로 20분간 적용했을 때가 앞다리운동감각 기능과 신경가역성 인자 GAP-43 발현에 가장 좋은 조건임을 알 수 있었다.